(untitled) (Italian Journal of Public Health, 2007)
Italian National Health Service (INHS) provides hospital, district and preventive cares in many medical areas but dental cares are a small part of all treatments provided. It is estimated that it only answers a 5% of need. In Italy dental treatments are predominantly provided by private practitioners: it means little access equity to cares. Nowadays, just 1,5% of the INHS expense is aimed at public dentistry because most of dental cares are believed “not urgent”. Why oral diseases are not considered so invalidating to have relief in INHS? They should get the same attention of the other pathologies because they worsen the quality of life in term of physical and psychological health. Need of public dentistry performances has recently increased, as confirmed by larger and larger waiting lists: it has revealed the growing dental need of the weakest part of the Italian society that, because of economic, social, cultural reasons, can hardly afford private cares (private practitioners are now facing a crisis, too). Dentists’ ethical code is not essentially different from physicians’ one even if most of the oral pathology is not worrying about patients’ life. “Bioethics in Dentistry” (2005), an issue by the National Bioethics Committee says: “public dentistry is actually absent in helping the weak part of the society. Just consider that in Italy oral cares are not included in Essential Care Levels (ECL) and they are not provided by Local Health Authorities whereas requirements to State exams include minimum tooth number and good oral health, because of the high importance of oral wellness.